2016
DOI: 10.1097/rlu.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

11C-Acetate PET/CT Monitoring Therapy of Multiple Myeloma

Abstract: A 67-year-old man with newly diagnosed multiple myeloma underwent both FDG and C-acetate PET/CT sequentially on different days. There was increased FDG activity only in L1 vertebral body, but there was diffuse abnormal C-acetate activity throughout the skeletal system. After the successful therapy, the patient who was on remission clinically underwent follow-up PET/CT scans. Interestingly, L1 remained to have elevated FDG, although with less intensity. In contrast, there was no abnormal C-acetate activity anyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…There have been some reports comparing AC-PET and FDG-PET in the clinical examination of MM. In two single-case reports, AC-PET appeared to be more sensitive than FDG-PET in assessing the tumor burden and/or response to therapy 16 , 17 . In addition, there only two cohort studies have been published to date, which compared these two imaging methods for this disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There have been some reports comparing AC-PET and FDG-PET in the clinical examination of MM. In two single-case reports, AC-PET appeared to be more sensitive than FDG-PET in assessing the tumor burden and/or response to therapy 16 , 17 . In addition, there only two cohort studies have been published to date, which compared these two imaging methods for this disease.…”
Section: Discussionmentioning
confidence: 96%
“…Some researchers have concluded that AC-PET outperformed FDG-PET in the diagnosis, risk stratification, and treatment monitoring of MM. However, the existing studies were limited due to the small number of participants 16 18 , and the correlation between AC-PET imaging analysis and MM prognosis is unclear 19 .…”
Section: Introductionmentioning
confidence: 99%
“…We propose that ACSS2 represents a novel therapeutic target for treating any tumor that has high ACSS2 expression and readily consumes acetate as an alternative nutrient source. Fortunately, 11 C-acetate PET is an established imaging tool in the clinic that has been extensively used for cancer detection (57)(58)(59)(60)(61)(62) and has also been used to study acetate-dependent fatty acid synthesis in preclinical models (15,52). 11 C-acetate PET imaging could easily be applied to help identify patients with cancer whose tumors are "hot" for acetate uptake.…”
Section: Discussionmentioning
confidence: 99%